Collaborative Governance Model in Promoting Budget Efficiency within the Regional Development Planning Process in Central Kalimantan - Akwila Trifena A. Awan; Zulkarnain; Beni Pramula; Mawar; Azhari Aziz Samudra (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze and formulate a collaborative governance model to promote budget efficiency in the regional development planning process in Central Kalimantan Province. The main problem in this study is the suboptimal budget efficiency caused by weak integration between planning and budgeting, a sectoral approach between regional government agencies, and low stakeholder participation in the planning process. This research used a qualitative approach with a case study design, supported by limited quantitative data. Data collection techniques included in-depth interviews, observation, documentation, and focus group discussions (FGDs). Informants were selected purposively and developed through snowball sampling. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing. The results indicate that regional development planning governance in Central Kalimantan has formally been implemented in accordance with regulations, but substantively remains ineffective and inefficient. The implementation of collaborative governance is still in its infancy, characterized by government dominance in decision-making, limited participatory dialogue, and low levels of trust between actors. These conditions have resulted in overlapping programs, inaccurate budget priorities, and mismatches between planning and budget realization. Based on these findings, this study develops a collaborative governance model that emphasizes multi-actor involvement, deliberative dialogue, information system integration, and collaborative leadership as key factors in increasing budget efficiency. This model is expected to produce more integrated, transparent, and community-based development planning. Theoretically, this research contributes to enriching the concept of collaborative governance in the context of regional development planning, while practically, it provides strategic recommendations for local governments to improve governance quality and budget efficiency. Therefore, implementing a collaborative governance model is crucial for achieving effective, efficient, and sustainable regional development.